Does Contracting-Out Primary Care Services Work? The Case of Rural Guatemala - Julian Cristia; William Evans; Beomsoo Kim (Inter-American Development Bank (IDB), 2011)
This paper estimates the impact of a large-scale contracting-out program in Guatemala, using two waves of living standard measurement surveys which collected data before and after the expansion of the program and exploiting variation in the timing of the program to estimate treatment effects. Results indicate large program impacts on immunization rates for children and prenatal care provider choices. The program increases substantially the role of physician and nurses as prenatal care providers at the expense of traditional midwives. There is no evidence of effects in family planning outcomes. Taken together these results suggest a potential effective role of contracting-out in the provision of health care.
Keywords: I12; I18; 330